Late Bronze and Early Iron Age copper smelting technologies in the South Caucasus: the view from ancient Colchis c. 1500–600 BC - Erb-Satullo, N; Gilmour, B; Khakhutaishvili, N (Elsevier, 2014)
Many of the arguments for how and why people began to use iron in Southwest Asia rely on assumptions about the technology and relative organization of copper and iron smelting. However, research on the technological transformations of the Late Bronze Age and Early Iron Age suffers from a lack of investigation of primary metal production contexts, especially in regions outside the Levant. The current research examines metal production debris from a large number of smelting sites in western Georgia, and addresses questions of technology and resource utilization through detailed examination of few select sites. Through the chemical and mineralogical analysis of slag samples, we demonstrate the existence of an extensive copper-production industry and reconstruct several key aspects of the smelting technology during the Late Bronze Age and Early Iron Age. Combining a statistical analysis of slag mineralogy with other lines of evidence, we argue that copper was extracted from sulfide ores through a process of roasting and smelting in deep pit furnaces. The data also suggest that metalworkers at different sites exploited different ore sources within the same ore body. These results form a fundamental basis for further examination of spatial and chronological patterns of technological variation, with implications for models of Near Eastern copper production in this crucial period. Intriguing evidence of bloomery iron smelting, though currently undated, reinforces the region's potential to provide data on a key technological transformation.